Electron transport in a silicon crystal observed by energy transfer luminescence. (29th July 2020) - Kojima, Osamu; Ito, Yukako; Kita, Takashi; Shim, Yong-Gu
Abstract: Observations of electron diffusion in semiconductor crystals is considerably important to improve device performance. This study investigates electron diffusion based on the observation of luminescence from a cyanine thin film fabricated on a semiconductor substrate. When the backside of the substrate was excited by laser light, enlarged intensity profiles, 20 times larger than the laser spot, were observed. An analysis of the spatial enlargement suggests that the enlargement originated from electron diffusion. This method can be used for analyzing electron transport and contributes to the development of emission devices based on energy transfer.